(untitled) (Research, Society and Development, 2021)
In the last century, the progress of studies related to medications has made it possible to combat some ills that affect humanity, however it is estimated that 80% of the population seeks alternative therapies, since the difficulty in having access to basic health services, either due to high the demand from patients or even the high cost of purchasing drugs makes them more often seek treatments with herbal medicines that are among the resources of complementary medicine and have been used for a long time by the population. Ginkgo has been used for centuries by traditional Chinese medicine to improve alertness. The research sought to carry out a bibliographic survey on the main interactions between drugs and herbal medicines made from ginkgo (Ginkgo biloba L.). The study was carried out through a systematic review, considering the relevance of the theme, seeking to know under the eyes of some authors as well as analyzing how and what are the drug interactions of the herbal medicine G. biloba. The elaboration of the research was based on material already published on the topic; scientific articles in periodic publications and available in the following databases: Scielo and Pubmed, considering articles published between 2010-2020, which reported on the possible drug interactions of the herbal medicine G. biloba. From the bibliographic research carried out, a total of 497 articles were published between the years 2010 to 2020. After reading, seven papers were selected, starting exhaustive readings of the texts, making a synthesis of each article and categorizing the types of drug interactions related to G. biloba.